Berpikir Ilmiah Siswa dalam Pembelajaran IPA Untuk Meningkatkan Literasi Sains - Ria Wulandari (Universitas Muhammadiyah Sidoarjo, 2017)
This research aimed to review students’ scientific thingking in science learning and in terms of increasing science literacy. The research method used was descriptive qualitatively and the data was collected using literature study. Research finding showed that students’ scientific thinking in science learning is conducted by the way of their thinking and acting in dealing with problems that exist in the environment. While, science literacy can be improved by raising students’ scientific thingking skill. By increasing students’ scientific reasoning, the students are be able to have well-ordered and accurate scientific reviewing skill.